Is Gray Matter Volume an Intermediate Phenotype for Schizophrenia? A VBM Study of Patients with Schizophrenia and their Healthy Siblings - Honea, Robyn A. (2007)
OBJECTIVE: Shared neuropathological characteristics of patients with schizophrenia and their siblings may represent intermediate phenotypes that could be used to investigate genetic susceptibility to the illness. We sought to discover previously unidentified gray matter volume differences in patients with schizophrenia and their siblings using optimized Voxel-Based Morphometry (VBM). METHODS: We studied 169 patients with schizophrenia, 213 of their unaffected siblings, and 212 healthy volunteers from the CBDB/NIMH Genetic Study of Schizophrenia with magnetic resonance imaging (MRI). RESULTS: Patients with schizophrenia had significant regional gray matter decreases in the frontal, temporal, and parietal cortices compared with healthy volunteers. Their unaffected siblings tended to share gray matter decreases in the medial frontal, superior temporal and insular cortices, but these decreases were not significant after correction for multiple comparisons, even when we looked at a subgroup of siblings with a past history of mood disorder. As an exploratory analysis, we estimated heritability using regions of interest from the VBM analysis, as well as from the hippocampus. Hippocampal volume was significantly correlated within sibling-pairs. CONCLUSIONS: Our findings confirm and extend previous VBM analyses in ill subjects with schizophrenia. Furthermore, these data argue that while siblings may share some regional gray matter decreases with their affected siblings, the pattern of regional differences may be a weak intermediate phenotype for schizophrenia.